A Contrastive Analysis of the Segmental Phonological Features of English and Twi (ʧwi) - Yekeen, BELLO (Global Journal of Social Sciences Studies, 2017)
This study attempted a Contrastive Analysis study of English language and Twi /ʧwi/ sound systems i.e. the segmental phonological features, with a view to finding out areas of similarities and differences in order to be acquainted with the possible areas of ease and difficulty for Ashanti learners of English as a second language. Findings showed that areas of similarities would not pose any problem for Ashanti learners of English while areas of differences would pose problems in English as a second language. Based on the findings and the conclusion, it was recommended that teachers of English should be aware of the need to concentrate more on speech training, speak, and in turn encourage their students to often speak English, as well as carrying out exercises on error analysis. Similarly, students are advised to cultivate the habit of good listening and speaking habits. They should also listen to both local and international news such as on the British Broadcasting Cooperation (BBC), Voice of America (VOA), among others with a view to making comparative analysis among them. It was also recommended that government should make oral English compulsory at all levels of academic institutions, among other recommendations.